PSYCHOMETRIC ANALYSIS OF THE SHORT VERSION OF ATTITUDES TOWARD LESBIANS AND GAY MEN SCALE (ATLG-S) (Annual of the Faculty of Philosophy in Skopje, 2019)
This study aims to examine the psychometric properties of the short versionof Attitudes Toward Lesbians and Gay Men Scale (ATLG) translated in Macedonianlanguage. A total of 500 undergraduate students who study 5 different disciplenes(Medicine, Stomatology, Psychology, Special education and rehabilitation andSocial work) participated voluntarily by providing answers to several questionnaires:the target instrument (ATLG-S) Transphobia Scale (TS)), Eight Item EmpathyQuotient test, the short version of the Scale of Dominance Orientation (SDO) andthe short version of Trust scale.The analysis of data suggest that the internal consistency of the ATLG-S isacceptable, both for the whole instrument (α=.90) and for the lesbian (α=.84) andgay subscales (α=.74). In addition, the principal components analyses followed byoblimin rotation extracted a two-factor solution of the instrument internal structure.Although not in line with the previous findings, this structure might be explainedand considered as adequate. The known-groups, convergent and divergent validityexamination have confirmed that the ATLG Scale is a valid and reliable measureof homonegativity and strongly support its use as a research instrument amongstudents and practitioners in the helping professions.
Keywords: PSYCHOMETRIC ANALYSIS; HOMOPHOBIA; HELPING PROFESSIONS; ATLG-S